Psychotherapists' experiences of using the sequentially planned integrative counselling for children model - Nortje, Elsabé (University of the Free State, 2016)
Every day, a large number of South African children are exposed to risk factors despite human rights assuming a prominent role in our country‟s constitution. Epidemiological studies indicate that approximately one in five children suffer from a mental disorder which often persists into adulthood. As mental health problems pose major risks for public health, childhood and adolescent mental health services assume a central role in reducing mental disorders. Early childhood intervention is therefore deemed essential and the need for therapeutic approaches to treat childhood mental disorders effectively have been highlighted. The most contemporary notion in working with children therapeutically includes selecting from an array of practice methods in order to attain the best possible outcomes in the most economical way. An example of an integrative model that draws on various therapeutic approaches is the Sequentially Planned Integrative Counselling for Children (SPICC) model. This model integrates diverse theoretical frameworks and practical strategies belonging to various other well-established psychotherapeutic approaches with its associated theory of change. These approaches include Client-Centred Psychotherapy, Gestalt Therapy, Narrative Therapy, Cognitive Behaviour Therapy, and Behaviour Therapy. An extensive review of the literature on the SPICC model produced limited published articles on research conducted internationally; with no published articles in South Africa. To fill the gap in the literature, the aim of this study was to explore and describe the experiences of South African psychotherapists using the SPICC model to counsel children. A qualitative multiple case study approach was chosen to elicit complex and rich descriptions made by the participants on their experiences of using the model. Three participants were recruited by means of purposeful sampling. Data was collected through individual research interviews and participants‟ reflections. From the data analysis six main themes emerged: 1) the SPICC model enhances psychotherapists‟ conceptualisation skills; 2) help clients faster; 3) the SPICC model requires and raises awareness of a therapeutic process; 4) the SPICC model enriches personal experiences; 5) the SPICC model‟s applicability within the South African context and 6) critique against the SPICC model. By describing participants‟ experiences, this study aimed to address the paucity of South African research on using the SPICC model in child therapy. The insights gained from the research findings highlighted the SPICC model‟s applicability to the South African context, as well as its potential to be used by novice psychotherapists. The research findings have crucial implications for psychotherapists who counsel children, as well as higher education professionals who can teach and supervise the SPICC model to students and novice psychotherapists.

ŉ Groot aantal Suid-Afrikaanse kinders word daagliks blootgestel aan risikofaktore, ongeag menseregte wat ŉ prominente rol in ons land se grondwet aanneem. Epidemiologiese studies het aangetoon dat ongeveer een uit vyf kinders aan ŉ psigiese versteuring ly wat meestal tot in volwassenheid duur. Aangesien psigiese gesondheidsprobleme groot risiko‟s inhou vir openbare gesondheid, moet kinder- en adolessente geestesgesondheidsdienste ŉ sentrale rol speel in die vermindering van psigiese versteurings. Vroeë kinderjare intervensie word dus as noodsaaklik gesien en die behoefte aan terapeutiese benaderings om psigiese versteurings tydens kinderjare effektief te behandel, word beklemtoon. Die mees kontemporêre neiging tydens terapeutiese werk met kinders, sluit ŉ wye reeks praktyk metodes in, wat ten doel het om die beste moontlike uitkomste op die mees ekonomiese manier te behaal. ŉ Voorbeeld van ŉ geïntegreerde model wat op verskeie terapeutiese benaderings geskoei is, is die Sequentially Planned Integrative Counselling for Children (SPICC) model. Hierdie model met sy verwante teorie van verandering, integreer diverse teoretiese raamwerke en praktiese strategieë wat gesetel is in verskeie ander goed-gevestigde psigoterapeutiese benaderings. Hierdie benaderings sluit in: Kliëntgesentreerde Psigoterapie, Gestalt Terapie, Narratiewe Terapie, Kognitiewe Gedragsterapie en Gedragsterapie. ŉ Omvattende oorsig van die literatuur met betrekking tot die SPICC model het ŉ beperkte aantal gepubliseerde artikels rakende navorsing wat oorsee uitgevoer is, opgelewer; met geen gepubliseerde artikels in Suid-Afrika nie. Die doel van die studie was om die ervarings van Suid-Afrikaanse psigoterapeute wat die SPICC model gebruik tydens terapie met kinders, te verken en te beskryf ten einde hierdie gaping in die literatuur te vul. ŉ Kwalitatiewe veelvuldige gevallestudie-benadering is gekies om komplekse en ryk beskrywings wat deur deelnemers gemaak word rakende hul ervarings in die gebruik van die model, te ontlok. Drie deelnemers is gewerf deur middel van doelgerigte steekproefneming. Data is ingesamel deur die individuele navorsingsonderhoude en die deelnemers se refleksies. Die data-analise het ses hooftemas opgelewer: 1) die SPICC model bevorder psigoterapeute se konseptualiseringsvermoë; 2) kliënte word vinniger gehelp; 3) die SPICC model bevorder en verhoog bewusmaking van ŉ terapeutiese proses; 4) die SPICC model verryk persoonlike ervarings; 5) die SPICC model is van toepassing binne die Suid-Afrikaanse konteks en 6) die kritiek teenoor die SPICC model. Die studie het met die beskrywing van die deelnemers se ervarings ten doel gehad om die tekort aan Suid-Afrikaanse navorsing rakende die gebruik van die SPICC model in terapie met kinders, aan te spreek. Die insigte wat verkry is uit die navorsingsbevindinge het die toepaslikheid van die SPICC model in die Suid-Afrikaanse konteks beklemtoon, asook die model se potensiaal om deur beginner-psigoterapeute gebruik te word. Die navorsingsbevindings het indringende gevolge vir psigoterapeute wat berading met kinders doen, asook vir hoër opvoedkundige spesialiste wat die model aanbied vir studente en beginner-psigoterapeute, asook in hul supervisie daarvan.
Dissertation (M.A. Psychology))--University of the Free State, 2016
Keywords: Child counselling; SPICC model; Childhood mental health; Integrative psychotherapy; Practice models; Psychotherapist and patient